Micro Analysis of Yield Gap and Associated Constraints in Adoption of Wheat (Triticum aestivum L. emend. Fiori & Paol) Production Technologies in Bihar - N. V. Kumbhare, Anil Kumar, K. Singh3 S. Chowdhuary (Indian Journal of Extension Education, 2022)
....